2021
DOI: 10.1039/d1cc04847c
|View full text |Cite
|
Sign up to set email alerts
|

Self-crystallisation, an unexpected property of 45S5 Bioglass®

Abstract: Self-crystallisation of 45S5 Bioglass® was observed at room temperature and atmospheric pressure, without further processing, one year after fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…The improvement of the mechanical properties of Ge25%, which was reported that the mechanical properties improve in the crystalline state, makes it a strong candidate for medical applications, which is consistent with the results of the IR for this ratio 50 .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The improvement of the mechanical properties of Ge25%, which was reported that the mechanical properties improve in the crystalline state, makes it a strong candidate for medical applications, which is consistent with the results of the IR for this ratio 50 .…”
Section: Resultssupporting
confidence: 85%
“…The diffraction peaks of SCP confirmed by matching the cards 96-810-3588, 96-231-0557, 96-154-0706 and 96-153-0880 of COD database (Fig. 4 ), also very closed to the reported similar bioglass systems 48 50 . GeO 2 peaks matched accurately PDF2 card no 98-005-9625 for GeO 2 .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…These results suggest the combination of both the nanoreinforcements due to the phases and the characteristic mineralogical composition of the MMT-NPs@MgNPs-BV base of Al, Si, P, Na, Mg, F, O, and H …”
Section: Resultsmentioning
confidence: 81%
“…Figure 2 shows the characterizations of the MMT-NPs, MgNPs-BV, and MMT-NPs@MgNPs-BV. According to Figure 2a, the MMT-NPs@MgNPs-BV demonstrated crystalline phases from MMT-NPs and MgNPs-BV, containing peaks in (i) muscovite 2M1 (Al These results suggest the combination of both the nanoreinforcements due to the phases and the characteristic mineralogical composition of the MMT-NPs@MgNPs-BV base of Al, Si, P, Na, Mg, F, O, and H. 15 MMT-NPs@MgNPs-BV obtained a lower d c of around 12.52 nm compared to the phases of 48 nm and 34 nm for MMT-NPs and MgNPs-BV, respectively, and a higher crystallinity at 82.02%. In this sense, the thermal treatment used, 1273.15 K, promoted an increase in the coalescence process, indicating greater organization of atoms, denoting greater mechanical strength, which is necessary for nanoreinforcements in nanocomposites.…”
Section: Resultsmentioning
confidence: 88%